Zirconium-niobium alloy composite electrode and preparation method and application thereof
By using zirconium-niobium alloy composite electrodes, the problem of insufficient electrode stability and depolarization ability during electrochemical liquor aging and electrochemical algae depletion process is solved, and efficient and stable electrochemical reactions are achieved, ensuring the quality of liquor and the efficiency of algae inactivation.
Patent Information
- Application Number
- CN202411635584.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
AI Technical Summary
The existing electrodes have low stability and insufficient depolarization ability in the aging of electrochemical liquor and electrochemical algae elimination process, resulting in electrode corrosion and damage to the acid-base balance of water, and insufficient adsorption capacity of flavored substances and algae in the liquor, affecting efficiency.
The zirconium-niobium alloy composite electrode is used to accurately control the composition, structure and surface state of the electrode to improve its chemical stability and polarization ability. This electrode is prepared by hydrothermal reaction and heat conversion treatment, and has high corrosion resistance and efficient polarization properties.
The high stability and efficiency of electrodes during the aging of electrochemical liquor and electrochemical algae destruction process are achieved, ensuring the quality stability of liquor and the algae inactivation efficiency, and avoiding electrode corrosion and the damage of acid and alkali balance in water.
Smart Images

Figure CN119506876A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemical technology, and in particular to a zirconium-niobium alloy composite electrode and a preparation method and application thereof. Background Art
[0002] Electrochemical technology is increasingly used in the fields of environment, food, energy, etc. Electrodes play a vital role in the application of electrochemical technology because they are the place where electrochemical reactions occur and directly affect the efficiency and selectivity of the reactions.
[0003] The aging of liquor is mainly a physical process in which water, ethanol and its flavor substances in the liquor body associate under weak intermolecular interactions (such as hydrogen bonds and van der Waals forces), and its chemical composition hardly changes. This association process gradually eliminates the irritation and spiciness of liquor, making it soft and pure sweet. Recently, electrochemical technology has been gradually applied to the aging of liquor, shortening the aging time while ensuring the quality stability of liquor. Among them, the electrode is the key. However, due to the low stability, strong depolarization ability and high catalytic activity of the electrode itself, the electrode corrodes during the electrochemical aging of liquor, and on the other hand, it catalyzes the electrochemical redox reaction of some substances in the liquor, changing the chemical composition of the liquor. Therefore, the electrochemical aging of liquor requires the use of an inert electrode with high stability and strong polarization ability. At the same time, the electrode has a strong adsorption capacity for the flavor substances in the liquor, promoting their aggregation on the electrode surface, thereby inducing their association on the electrode surface through electrochemical polarization, accelerating the aging of liquor.
[0004] The electrochemical method has potential advantages in controlling algae outbreaks. This method uses various active free radicals generated by electric current or electrochemical oxidation under the action of an electric field to destroy the cell structure of algae and inactivate them. This generally requires the electrode to apply a large potential, but this will cause oxidative corrosion of the electrode itself, shortening its service life. On the other hand, it will also cause electrolysis of water and destroy the acid-base balance of the water body. In addition, the general electrode has a weak adsorption capacity for algae, resulting in low algaecide efficiency. Therefore, electrochemical algaecide also requires an electrode with a wide electrochemical window and good chemical stability in the water body. Special treatment of the electrode surface may be required to enhance its adsorption and inactivation capacity for algae.
[0005] Therefore, whether it is electrochemical liquor aging or electrochemical algae removal, the preparation of electrodes is a key step, and the performance of electrodes needs to be designed and optimized according to specific application requirements. The application effect of electrochemical technology can be improved by precisely controlling the composition, structure and surface state of the electrodes. Summary of the invention
[0006] The present invention provides a zirconium-niobium alloy composite electrode and a preparation method and application thereof, aiming to solve the problems existing in the above-mentioned background technology.
[0007] To achieve the above purpose, the present invention mainly adopts the following technical solutions:
[0008] In a first aspect, the present invention discloses a method for preparing a zirconium-niobium alloy composite electrode, comprising the following steps:
[0009] (1) Processing the raw material of zirconium-niobium alloy ingot into metal sheets, polishing the surface and then ultrasonically cleaning it;
[0010] (2) placing the metal sheet into an autoclave, adding a mixed salt solution to perform a hydrothermal reaction, cooling, and taking out the metal sheet after the reaction;
[0011] (3) The metal sheet after the reaction is subjected to thermal conversion treatment to obtain a zirconium-niobium alloy composite electrode.
[0012] In a preferred embodiment of the present invention, the raw material of the zirconium-niobium alloy ingot comprises: a zirconium content of 19-99% by mass and a niobium content of 1%-81% by mass.
[0013] Preferably, the raw material of the zirconium-niobium alloy ingot comprises: a zirconium content of 998% by mass and a niobium content of 2% by mass.
[0014] In a preferred embodiment of the present invention, the mixed salt solution comprises a metal salt, deionized water and a pH regulator, the metal salt is a zirconium salt and a niobium salt, and the molar ratio of the metal salt to the deionized water is 0.2 to 5:1000.
[0015] Preferably, the zirconium salt is selected from any one or more of Zr(SO4)2, Zr(NO3)4·5H2O, and ZrCl4; the niobium salt is selected from any one or more of niobium oxalate, niobium acetate, niobium nitrate, niobate, and NbCl5; and the pH adjuster is selected from any one or more of sodium hydroxide, hexamethylenetetramine, and triethylamine.
[0016] Preferably, the molar ratio of the zirconium salt to the niobium salt is (2-4):1.
[0017] Preferably, the pH adjuster adjusts the pH of the mixed salt solution to 8.5-10.0.
[0018] In a preferred embodiment of the present invention, the hydrothermal reaction temperature is 90-200°C, the constant temperature time is 6-48 hours, the heating rate is 5-20°C / min, and the cooling is natural cooling.
[0019] In a preferred embodiment of the present invention, the heat conversion treatment conditions are: under inert atmosphere protection conditions, at a temperature of 300 to 700° C. for 2 to 7 hours.
[0020] In a second aspect, the present invention discloses a zirconium-niobium alloy composite electrode prepared by the preparation method described in the first aspect.
[0021] In a third aspect, the present invention discloses an application of the zirconium-niobium alloy composite electrode described in the second aspect in electrochemical liquor aging or electrochemical algae removal.
[0022] Specifically, when applied to electrochemical liquor aging, the following method is adopted:
[0023] The zirconium-niobium alloy composite electrode is used as a working electrode, and a platinum sheet electrode is used as a reference electrode and an auxiliary electrode to form an electrode system, and a high voltage is applied to the working electrode in the liquor to treat the liquor;
[0024] Among them, the polarization voltage of the working electrode is ±2-8V (vs.Pt), and the polarization treatment time is 7-20 days.
[0025] When applied to electrochemical algae removal, the following method is used:
[0026] The zirconium-niobium alloy composite electrode is used as a working electrode, and another zirconium-niobium alloy composite electrode of the same area is used as a reference electrode and an auxiliary electrode to form an electrode system, the two electrodes are placed in a water body containing cyanobacteria, and a high voltage is applied to the working electrode to treat the water body;
[0027] The polarization voltage of the working electrode is ±3-5V, and the polarization treatment time is 1-30 minutes.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The zirconium-niobium alloy composite electrode provided by the present invention has a high chemical stability by precisely controlling the composition, structure and surface state of the electrode. These unique chemical compositions and microstructures make the electrode suitable for different medium environments. At the same time, the electrode has a high polarization ability, and a certain voltage is applied to cause the substance on the electrode surface to directly undergo an electrolytic reaction. The electrode is applied to the electrochemical aging of liquor and electrochemical algae removal, and has good effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The present invention will be further described in detail below in conjunction with the accompanying drawings and preferred embodiments, but those skilled in the art will appreciate that these drawings are drawn only for the purpose of explaining the preferred embodiments and therefore should not be used as a limitation on the scope of the present invention. In addition, unless otherwise specified, the drawings are only schematically representing the composition or structure of the described objects and may contain exaggerated displays, and the drawings are not necessarily drawn to scale.
[0031] Figure 1 A microstructure diagram of a zirconium-niobium alloy composite electrode provided in Example 1 of the present application;
[0032] Figure 2 A comparison diagram of polarization curves of the zirconium-niobium alloy composite electrode provided in Example 1 of the present application and the original niobium alloy raw material in a sodium chloride medium;
[0033] Figure 3 This is a comparison diagram of the linear voltammetric scanning curves of the zirconium-niobium alloy composite electrode provided in Example 1 of the present application and the original niobium alloy raw material in white wine. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are protected by the present invention.
[0035] Example 1 Preparation of Zirconium-Niobium Alloy Composite Electrode 1
[0036] Commercial zirconium-niobium alloy ingot raw materials (98% zirconium content, 2% niobium content) were processed into metal sheets with a size of 50mm×20mm×2mm by wire cutting, and the surface was polished and then ultrasonically cleaned with ethanol. The metal sheet was placed in an autoclave, and a mixed salt solution containing ZrCl4 and NdCl5 (molar ratio 3:1) was added, and the molar ratio of salt concentration to deionized water was 1:1000. Hexamethylenetetramine was added to adjust the pH value to 9.0. The autoclave was heated at a rate of 10℃ / min, heated to 120℃ and kept warm for 14 hours, and then cooled naturally. The metal sheet was transferred to a tubular furnace, filled with argon gas, heat treated at 400℃ for 5 hours, and taken out for use, thereby obtaining a zirconium-niobium alloy composite electrode 1.
[0037] The microstructure of the zirconium-niobium alloy composite electrode 1 prepared in this embodiment was observed using a scanning electron microscope (SEM). Figure 1 As shown, from Figure 1 It can be seen that the zirconium-niobium alloy composite electrode 1 in this embodiment is formed with a microstructure, which helps to increase the specific surface area of the electrode and increase the adsorption capacity and reaction area of the electrode.
[0038] The polarization curves obtained by performing potentiodynamic scanning in a neutral 3.5% NaCl solution were compared with the zirconium-niobium alloy composite electrode 1 prepared in this embodiment and the original zirconium-niobium alloy raw material. Figure 2 As shown. Figure 2 It can be seen that compared with the original zirconium-niobium alloy raw material, the zirconium-niobium alloy composite electrode 1 prepared in this embodiment has a smaller corrosion current density in a 3.5% by mass NaCl solution than the original zirconium-niobium alloy raw material, indicating that the zirconium-niobium alloy composite electrode 1 has higher corrosion resistance and stability.
[0039] The zirconium-niobium alloy composite electrode 1 prepared in this embodiment and the original zirconium-niobium alloy raw material were linearly scanned in white wine. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that compared with the original zirconium-niobium alloy raw material, the zirconium-niobium alloy composite electrode 1 prepared using this embodiment has a higher initial oxidation potential in white wine and a smaller oxidation current at the same potential, indicating that the zirconium-niobium alloy composite electrode 1 has a weaker oxidation ability for white wine, and when it is used for aging white wine, it is not easy to cause an oxidation reaction in the white wine and cause the white wine to change its format.
[0040] Example 2 Preparation of Zirconium-Niobium Alloy Composite Electrode 2
[0041] Commercial zirconium-niobium alloy ingot raw materials (98% zirconium content, 2% niobium content) were processed into metal sheets with a size of 200mm×50mm×2mm by wire cutting. After surface polishing, they were ultrasonically cleaned with ethanol. The metal sheet was placed in an autoclave, and a mixed salt solution containing ZrCl4 and NdCl5 (molar ratio 2.5:1) was added. The molar ratio of salt concentration to deionized water was 1:300. Hexamethylenetetramine was added to adjust the pH value to 8.0. The autoclave was heated at a rate of 8℃ / min, heated to 150℃ and kept warm for 12 hours, and then cooled naturally. The metal sheet was transferred to a tubular furnace, filled with argon gas, heat treated at 400℃ for 3 hours, and taken out for use, thereby obtaining a zirconium-niobium alloy composite electrode 2.
[0042] Test Example 1 Application of Zirconium-Niobium Alloy Composite Electrode 1 in Liquor Aging
[0043] New distilled liquor samples from a certain company were selected for electrochemical aging treatment.
[0044] Experimental group: The zirconium-niobium alloy composite electrode 1 was used as the working electrode, and the platinum sheet electrode was used as the reference electrode and the auxiliary electrode to form an electrode system. The electrodes were placed in 500 mL of white wine. The distance between the working electrode and the auxiliary electrode was 1 cm. At the same time, a high voltage of 3 V was applied to the working electrode. The polarization time was 10 days to obtain aged white wine.
[0045] Control group: The difference from the experimental group is that gold is used as the working electrode and the other conditions remain unchanged.
[0046] The aged liquor in the test group was subjected to sensory evaluation. The evaluation team randomly selected 10 people from the research institute to conduct the sensory evaluation and took the average value. The results are shown in Table 1.
[0047] Table 1 Sensory evaluation of liquor
[0048] Color(10) Aroma(25) Flavor(50) Style(15) Total score (100) initial 9 19 33 14 75 Experimental Group 9 24 46 14 93 Control group 9 17 36 12 74 Natural aging for 3 years 9 23 46 15 93
[0049] It can be seen from Table 1 above that the liquor electrochemically aged by the zirconium-niobium alloy composite electrode of the present invention is basically consistent with the liquor naturally aged for 3 years in color, aroma, taste and quality, and can achieve the 3-year cellar aging effect.
[0050] The main component content, total acid and total ester of the initial liquor, the aged liquor of the test group and the control group were tested. The results are shown in Table 1 below.
[0051] Table 2 Contents of main components of liquor and initial liquor in the experimental group and control group
[0052] initial Experimental Group Control group Acetaldehyde (mg / 100mL) 47.85 44.71 71.20 n-Propanol (mg / 100mL) 57.24 61.44 38.63 Ethyl acetate (mg / 100mL) 331.58 342.56 207.36 Sec-Butanol (mg / 100mL) 9.92 10.47 8.33 Isobutanol (mg / 100mL) 7.03 7.49 6.27 n-Butanol (mg / 100mL) 57.81 58.93 37.36 Acetic acid (mg / 100mL) 94.86 95.40 139.72 Isoamyl alcohol (mg / 100mL) 21.07 21.95 15.14 Ethyl butyrate (mg / 100mL) 15.42 15.38 12.87 Ethyl lactate (mg / 100mL) 138.19 138.12 137.71 Ethyl valerate (mg / 100mL) 16.59 16.86 14.44 Ethyl hexanoate (mg / 100mL) 281.11 290.11 187.62 Alcohol content (%, V / V) 73.9 74.1 67.8 Total acid (g / L) 1.40 1.39 2.22 Total esters (g / L) 3.16 3.14 1.99
[0053] As shown in Table 2, the contents of the main components of the test example remain basically unchanged, indicating that the aging method using the zirconium-niobium alloy composite electrode 1 promotes the aging of liquor through a physical process without changing the substance type and content of the liquor, and can maintain the aroma and style of the liquor. However, in the control group, the concentrations of various alcohols, aldehydes and esters in the liquor changed significantly, and the alcohol content and total esters of the liquor also decreased significantly, and the total acid increased, indicating that the composition of the liquor in the control group has changed.
[0054] Test Example 2 Application of Zirconium-Niobium Alloy Composite Electrode 2 in Algae Removal in Water
[0055] A certain volume of water containing cyanobacteria is selected as the water sample to be treated and electrochemical algae removal is carried out.
[0056] A zirconium-niobium alloy composite electrode 2 is used as the working electrode, and another zirconium-niobium alloy composite electrode 2 is used as the reference electrode and the auxiliary electrode to form an electrode system. The distance between the working electrode and the auxiliary electrode is 1 cm. They are placed in 200 mL of the water sample to be treated, and a high voltage of 3 V is applied to the working electrode. The polarization time is 3 minutes to obtain the water body after algae removal.
[0057] The absorbance of the untreated water and the treated water was measured by ultraviolet spectrophotometer to evaluate the efficiency of electrochemical algae killing. The results showed that the algae killing rate in the treated water reached 100%.
[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a zirconium-niobium alloy composite electrode, characterized in that: The steps include: (1) Processing the raw material of zirconium-niobium alloy ingot into metal sheets, polishing the surface and then ultrasonically cleaning it; (2) placing the metal sheet into an autoclave, adding a mixed salt solution to perform a hydrothermal reaction, cooling, and taking out the metal sheet after the reaction; (3) The metal sheet after the reaction is subjected to thermal conversion treatment to obtain a zirconium-niobium alloy composite electrode.
2. The method for preparing a zirconium-niobium alloy composite electrode according to claim 1, characterized in that: The raw materials of the zirconium-niobium alloy ingot include: zirconium content of 19-99% by mass, and niobium content of 1%-81% by mass.
3. The method for preparing a zirconium-niobium alloy composite electrode according to claim 1, characterized in that: The mixed salt solution comprises metal salt, deionized water and a pH regulator, the metal salt is zirconium salt and niobium salt, and the molar ratio of the metal salt to the deionized water is 0.2-5:1000.
4. The method for preparing a zirconium-niobium alloy composite electrode according to claim 3, characterized in that: The zirconium salt is selected from any one or more of Zr(SO4)2, Zr(NO3)4·5H2O, and ZrCl4; the niobium salt is selected from any one or more of niobium oxalate, niobium acetate, niobium nitrate, niobate, and NbCl5; the pH regulator is selected from any one or more of sodium hydroxide, hexamethylenetetramine, and triethylamine.
5. The method for preparing a zirconium-niobium alloy composite electrode according to claim 3, characterized in that: The molar ratio of the zirconium salt to the niobium salt is (2-4):
1.
6. The method for preparing a zirconium-niobium alloy composite electrode according to claim 3, characterized in that: The pH regulator adjusts the pH of the mixed salt solution to 8.5-10.
0.
7. The method for preparing a zirconium-niobium alloy composite electrode according to claim 1, characterized in that: The hydrothermal reaction temperature is 90-200° C., the constant temperature time is 6-48 hours, the heating rate is 5-20° C. / min, and the cooling is natural cooling.
8. The method for preparing a zirconium-niobium alloy composite electrode according to claim 1, characterized in that: The heat conversion treatment conditions are: under inert atmosphere protection conditions, at a temperature of 300-700° C. for 2-7 hours.
9. A zirconium-niobium alloy composite electrode prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the zirconium-niobium alloy composite electrode as claimed in claim 9 in electrochemical liquor aging or electrochemical algae removal.